Cryotherapy for low rectal and anal cancer: recommendation and indications - Jiang, Xuejun; Ji, Zujin; Lei, Xinyi; He, Yingmei; Yuan, Fangjun (Frontiers in Oncology, 2023)
Low rectal cancer is a common gastrointestinal malignancy. How to preserve organs in the treatment of low rectal cancer is a problem that doctors need to pay attention to. In addition to surgical resection, freezing—a beneficial supplement to treat low rectal cancer—solved the problem that some patients cannot preserve the anus. However, it still lacks a unified standard on the cryosugery since the case reported. Our hospital have been doing cryotherapy for about 40 years since 1976. In our department, the indications and contraindications for low rectal and anal cancer are well stablished. In this paper, the indications and contraindications of colorectal cancer cryotherapy were summarized by reviewing the literature and our work experience, combined with the current imaging and histological techniques, so as to facilitate clinical discussion and promotion.